TRANSPORT OF RADIONUCLIDES IN AN UNCONFINED CHALK AQUIFER INFERRED FROM U-SERIES DISEQUILIBRIA - Hubert A.; Bourdon B.; Pili E.; Meynadier L. (My University, 2006)
U-series disequilibria measured in waters and rocks from a chalk aquifer in France have been used as an analog for long-term radionuclide migration. Drill core samples from a range of depths in the vadose zone and in the saturated zone, as well as groundwater samples were analyzed for 238U, 234U, 232Th and 230Th to determine transport mechanisms at the water/rock interface and to quantify parameters controlling the migration of radionuclides. Isotope measurements in rocks were done by TIMS, whereas (234U/238U) and (230Th/232Th) activity ratios in water samples were measured by multi-collector-ICP-MS. Both depletion and enrichment in 234U relative to 238U were observed in carbonate rock samples resulting from chemical weathering in the unsaturated zone and calcite precipitation in the zone of water-table oscillation, respectively. The correlation between (230Th/232Th) activity ratios and 87Sr/86Sr ratios found in the chalk samples indicates that thorium is mainly contained in a minor silicate phase whose abundance is variable in chalk samples. Water samples are all characterized by (234U/238U) > 1 resulting from ?-recoil effect of 234Th. Groundwaters are characterized by a more radiogenic signature in 87Sr/86Sr than the rocks. Moreover, (230Th/232Th) activity ratios in the waters are lower than in the rocks, and increase with distance from the water divide, which suggests that Th transport is controlled by colloids formed during water infiltration in the soil. A 1-D transport model has been developed in order to constrain the U-series nuclide transport considering a transient behavior of radionuclides in the aquifer and a time-dependent composition for the solid phase. This model permits a prediction of the time scale of equilibration of the system, and an estimation of parameters such as weathering rate, distribution coefficients and ?-recoil fractions. Retardation factors of 10-35 and from 1 ? 104 to 2 ? 105 were predicted for U and Th, respectively, and can be used to predict the migration of radionuclides released as contaminants in the environment. At the scale of our watershed (?32 km2), a characteristic migration time from recharge to riverine discharge of 200-600 yr for U and 0.2-3.7 Myr for Th was obtained. ? 2006 Elsevier Inc. All rights reserved.
Keywords: AQUIFER POLLUTION; INFILTRATION; ISOTOPIC COMPOSITION; POLLUTANT TRANSPORT; RADIONUCLIDE MIGRATION; RIVER DISCHARGE; UNCONFINED AQUIFER; WATERSHED